Engineering MXene based MWO4 (M = Cu, Ni, Co) catalysts for dual-functional photocatalysis: Insights into wastewater remediation and hydrogen production - Erdem, Nurseli Görener; Şimsek, Esra Bilgin (Elsevier B.V., 2025)
In recent years, MXenes have gained considerable attention as emerging photocatalysts due to their unique physicochemical and optical properties. In the current study, Ti?C? type MXene was successfully hybridized with transition metal tungstates (MWO4, M: Cu, Ni, Co) to fabricate novel composite photocatalysts. The synthesized materials were characterized using SEM/EDX, HR-TEM, XRD, XPS, AFM, EPR, UV–Vis DRS, FTIR, Raman, PL and electrochemical analyses. The influence of transition metal types on structural, optical, and photocatalytic properties was systematically examined. The incorporation of MWO4 with MXene structure improved the light-harvesting capacity, charge separation efficiency, and electrochemical performance of the pristine counterparts. The enhancement was attributed to the synergy between MXene's layered structure –providing high surface area– and the metal tungstates’ strong visible-light absorption. The photocatalytic performance was evaluated towards tetracycline degradation under visible light and the removal efficiencies of MX-CoW, MX-NiW and MX-CuW composites were found to be 1.2, 1.3 and 1.5 times higher than that of the pristine MXene. Furthermore, the composites displayed enhanced hydrogen evolution rates which were determined as 1997, 1947, and 1940 µmol/gcat.h, respectively. The improved photocatalytic performance was ascribed to Z-scheme charge transfer mechanism, which promoted spatial charge separation and suppressed the recombination of photoinduced carriers. Additionally, the composites demonstrated good recyclability over multiple reaction cycles. This study provides promising insight into the rational design of MXene-based heterostructures for integrated applications in environmental remediation and sustainable hydrogen production. © 2025 Elsevier B.V., All rights reserved.
Keywords: Hydrogen; Metal tungstate; MXene; Photocatalysis; Z-scheme heterojunction